Investigation of FADS Gene Cluster Single Nucleotide Polymorphisms in End-Stage Renal Disease Compared With Normal Controls - Miladipour, Amirhossein; Gholipour, Mahdi; Honarmand Tamizkar, Kasra; Abak, Atefe; Kholghi Oskooei, Vahid; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Genetics, 2021)
End-stage renal disease (ESRD) is a public health problem with high burden. This condition is associated abnormalities lipid metabolism. Fatty acid desaturase (FADS) gene cluster includes three genes which are significantly correlated with a number of pathologic conditions related with abnormal lipid levels. In the current study, we genotyped rs174556, rs99780 and rs7115739 single nucleotide polymorphisms within FADS cluster in a population of ESRD patients and healthy controls. The rs174556 of FASD1 gene and rs99780 of FASD2 gene were not associated with risk of ESRD in any inheritance model. However, the rs7115739 of FASD3 was associated with risk of ESRD in all models except for recessive model. T allele of this SNP was significantly less prevalent among cases compared with controls (Odds ratio (OR) [95% CI] = 0.44 [0.25-0.77], P value=0.004). GT and TT genotypes has been shown to decrease risk of ESRD in codominant model (OR [95% CI] = 0.49 [0.26-0.92] and OR [95% CI] = 0.18 [0.02-1.6], respectively; P value=0.019). In dominant model, GT+TT status was associated with lower risk of ESRD (OR [95% CI] = 0.45 [0.24-0.82], P value= 0.0078). Assessment of association between this SNP and risk of ESRD in overdominant model revealed that GT genotype decreases risk of this condition (OR [95% CI] = 0. 5 [0.27-0.94], P value=0.029). Taken together, the rs7115739 of FASD3 is suggested as putative modulator of risk of ESRD in Iranian population.